Aerosol Effects on Lightning Characteristics: A Comparison of Polluted and Clean Regimes. Issue 9 (30th April 2020) - Liu, Y.; Guha, A.; Said, R.; Williams, E.; Lapierre, J.; Stock, M.; Heckman, S.
Abstract: Oceanic lightning can be a sensitive indicator of aerosol effects on lightning characteristics as thermodynamic contrast is indistinct over adjacent oceanic regions. The study presents discernable aerosol impacts on lightning characteristics by analyzing 2 years (2017–2018) of intracloud (IC) and cloud‐to‐ground (CG) lightning data from Earth Networks Total Lightning Network over two key regions in southern South China Sea. Mean stroke density, IC/CG ratio, +IC fraction, and +CG fraction in polluted conditions are respectively 3.7, 2, 1.2, and 5.8‐fold larger than unpolluted counterparts. Total stroke contrast is further confirmed with the GLD360 network. Thermodynamic parameters conversely support slightly stronger convection over clean ocean. Clear evidence shows cloud droplet size diminishes with added aerosol. Aerosol invigorates more frequent and robust mixed‐phase development, endowing maritime convection with continental characteristics. Modifications in the charge reversal temperature and lower and upper positive charge regions are speculated on as means for stimulating more positive ICs and CGs. Plain Language Summary: Over adjacent oceanic regions, the thermodynamic contrast is indistinct, and this makes oceanic lightning a sensitive indicator of aerosol effects. The southern South China Sea, surrounded by wideband electric‐field sensors in Earth Networks Total Lightning Network, is focused on the response of both intracloud (IC) and cloud‐to‐ground (CG) strokes to added aerosol over 2 years (2017–2018). The thermodynamic and cloud microphysical parameters are quantitatively analyzed between polluted and clean oceanic regions. Distribution maps of sulfur dioxide and aerosol optical depth show clear locations for polluted regions. Mean stroke density, IC/CG ratio, +IC fraction, and +CG fraction in polluted conditions are respectively 3.7, 2, 1.2, and 5.8‐fold larger than the unpolluted counterparts, while thermodynamic parameters conversely support slightly weaker convection over polluted regions and discount its effects in supporting lightning enhancement. Added aerosol decreases cloud effective particle radius of ice and liquid water based on satellite measurement. Larger lower and upper positive charge reservoirs invigorated by the energized graupel‐ice crystal electrification process and possible modification of the charge reversal temperature are speculated as mechanisms to promote more positive strokes. More frequent and robust mixed‐phase development favorable for lightning is stimulated by added aerosol over ocean, endowing maritime convection with continental characteristics. Key Points: Oceanic lightning can be a sensitive indicator of aerosol effects on lightning characteristics as the thermodynamic contrast is indistinct or even supports weaker convection in the polluted region Mean stroke density, IC/CG ratio, +IC fraction, and +CG fraction in the polluted oceanic region are respectively 3.7, 2, 1.2, and 5.8 ‐fold larger than the adjacent unpolluted oceanic counterparts Aerosol provides for more frequent and robust mixed‐phase development, endowing maritime convection with continental characteristics